2010
DOI: 10.1530/eje-09-0880
|View full text |Cite
|
Sign up to set email alerts
|

High-dose GH treatment limited to the prepubertal period in young children with idiopathic short stature does not increase adult height

Abstract: Objective: To assess the long-term effect of prepubertal high-dose GH treatment on growth in children with idiopathic short stature (ISS). Design and methods: Forty children with no signs of puberty, age at start 4-8 years (girls) or 4-10 years (boys), height SDS !K2.0 SDS, and birth length OK2.0 SDS, were randomly allocated to receive GH at a dose of 2 mg/m 2 per day (equivalent to 75 mg/kg per day at start and 64 mg/kg per day at stop) until the onset of puberty for at least 2 years (preceded by two 3-month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Additional potential advantages of lowering the overall GH exposure in the treatment of ISS patients include a theoretical reduction of the risk of side effects and a lower risk of rapid acceleration of skeletal maturation [24,25], although it should be noted that we did not observe any differences in either the safety profile or the rates of skeletal maturation or pubertal advancement between the dose groups during the 4-year course of this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Additional potential advantages of lowering the overall GH exposure in the treatment of ISS patients include a theoretical reduction of the risk of side effects and a lower risk of rapid acceleration of skeletal maturation [24,25], although it should be noted that we did not observe any differences in either the safety profile or the rates of skeletal maturation or pubertal advancement between the dose groups during the 4-year course of this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an extensive Pubmed search including recent reviews [5,9,[13][14][15]], we have not been able to find studies dealing specifically with the start of rhGH administration at the very end of puberty in ISS. Indeed, most studies had focused on prepubertal children [3,5,9,[13][14][15][22][23][24]27,37]. As an example, the study that allowed rhGH to gain acceptance for ISS by the FDA [24] excluded boys with a bone age greater then 13 years and a testicular volume larger then 10 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical effectiveness of recombinant human growth hormone (rhGH) in ISS is well documented [3,5,[13][14][15][22][23][24]27,37], the use of this treatment varies largely across countries and health systems. For example the treatment of ISS with rhGH is not approved by the European Medicine Agency, whereas this indication has been approved in the United States since 2003, followed by a consensus on the management of ISS published in 2008 [9].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, van Gool et al ( 79 ) have reported that high dose GH therapy in prepubertal children with ISS does not improve adult height, as it increases height gain during treatment but, at the same time, accelerates bone maturation, resulting in a similar adult height compared with the untreated controls.…”
Section: Introductionmentioning
confidence: 99%